Peluang Bisnis Aromatik Parfum dalam Era Digitalisasi: Implikasi Strategi Pemasaran, Inovasi Produk, dan Pengembangan Kewirausahaan Mahasiswa - Eka Dwi Yanti; Muhammad Arif (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2026)
In the era of digitalization, many business opportunities have emerged in various industrial sectors, one of which is the creative industry that has become a popular business idea among young entrepreneurs, especially Generation Z. The creative industry that is increasingly sought after in a business is aromatic perfumes, which indicates a significant growth marked by the increasing consumer demand for fragrance products in the market every year. The perfume industry presents promising business opportunities considering the high market demand for fragrance products with various aroma variations and benefits. This research aims to analyze the implications for marketing strategies, product innovation, and the development of entrepreneurship among students in the era of digitalization. By using a descriptive qualitative approach through literature studies, interviews, and observations of digital market trends, the results of this study indicate that the utilization of digital platforms such as social media and E-commerce can enhance the competitiveness of products. Innovations provided in aroma, packaging, and product personalization become some of the attractive factors for consumers. In addition, support and entrepreneurship training can encourage students' enthusiasm in developing businesses. Keywords: Marketing Strategy, Product Development Innovation, Student Entrepreneurship Development.